Fuzzy Tahani Model for Selection Journal Computer Sciences and Technology (Sinta 2): Across Indonesia - Wantoro, Agus; Hari Soetanto; Dikpride Despa; Tahta Herdian Andika (Faculty of Engineering, Universitas Brawijaya, 2025)
Publication of scientific articles in the national journal Science and Technology (Sinta) has become an obligation for academics such as students and lecturers. For students, publication is one of the requirements for graduation. For lecturers, scientific publication is a requirement for promotion or academic level (JA). Several levels of JA are Assistant Expert, Lecturer, Senior Lecturer and Professor. Lecturers who will apply for promotion to Senior Lecturer are required to publish in the Sinta 2 Journal. To be able to find a suitable journal, there are many considerations, if you choose the wrong journal, the article can be rejected. In choosing a journal, authors generally look at information such as publication costs, number of articles published, number of article publication frequencies, and review process time. Sometimes authors need ambiguous information such as the number of articles with many categories, low costs, high publication frequencies, and fast review times. The approach to this problem can use the Tahani fuzzy model database. This study applies the Tahani fuzzy model to model Sinta 2 journal data in the computer field to provide new findings and facilitate the selection of journals that match the criteria. This research needs to be done to provide useful information for several parties. For the author, this research is useful as a reference for selecting journals according to the criteria sought. For journal managers or editors, this information can increase the number of articles to be published, and for further researchers, this research will be information and reference material regarding journal selection research